2018
DOI: 10.1186/s12877-018-0801-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the WeCareAdvisor™ on family caregiver outcomes in dementia: a pilot randomized controlled trial

Abstract: BackgroundBehavioral and psychological symptoms of dementia (BPSD) are universal and associated with multiple negative outcomes. This pilot randomized controlled trial (RCT) evaluated the effect of using the WeCareAdvisor, an innovative web-based tool developed to enable family caregivers to assess, manage, and track BPSD.MethodsThis RCT enrolled 57 dementia family caregivers from community and clinical settings in Ann Arbor, Michigan and Baltimore, Maryland. Participants were randomly assigned to immediate us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
106
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(110 citation statements)
references
References 28 publications
1
106
0
3
Order By: Relevance
“…The intervention duration ranged from 4 weeks to 12 months. Eight studies were performed in the United States [ 25 , 26 , 31 , 38 , 41 , 42 , 44 , 46 ], 3 studies were performed in Netherlands [ 28 , 37 , 40 ], 2 studies were performed in France [ 29 , 43 ], and 1 study each was conducted in Canada [ 39 ], Germany [ 30 ], Spain [ 27 ], and the UK [ 45 ]. All of the included studies reported clear inclusion and exclusion criteria for their participants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The intervention duration ranged from 4 weeks to 12 months. Eight studies were performed in the United States [ 25 , 26 , 31 , 38 , 41 , 42 , 44 , 46 ], 3 studies were performed in Netherlands [ 28 , 37 , 40 ], 2 studies were performed in France [ 29 , 43 ], and 1 study each was conducted in Canada [ 39 ], Germany [ 30 ], Spain [ 27 ], and the UK [ 45 ]. All of the included studies reported clear inclusion and exclusion criteria for their participants.…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies reported clear inclusion and exclusion criteria for their participants. In 9 studies, the forms of internet-based support interventions were personalized [ 25 , 27 , 28 , 40 - 42 , 44 - 46 ] whereas in the other 8 studies [ 26 , 29 - 31 , 37 - 39 , 43 ], they were nonpersonalized. The nature of the treatment of control group participants differed from one study to another.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations